Does the healthcare educational market respond to short-run local demand? - Marcus Dillender; Andrew Friedson; Thanh Cong Gian; Kosali Simon (W.E. Upjohn Institute for Employment Research, 2019)
The Patient Protection and Affordable Care Act (ACA) increased demand for healthcare across the U.S., but it is unclear if or how the supply side has responded to meet this demand. In this paper, we take advantage of plausibly exogenous geographical heterogeneity in the ACA in order to examine the response of the healthcare education sector to increased demand for healthcare services. We look across educational fields, types of degrees, and types of institutions; we pay particular attention to settings where our conceptual model predicts heightened responses. We find no statistically significant evidence of increases in graduates and can rule out fairly modest effects. This implies that healthcare production may have adjusted to increased demand from insurance expansion in other ways rather than primarily through new graduates from local healthcare educational markets.
Keywords: I13; I23; J21; 330; healthcare workforce; demand for schooling; educational pipeline; Affordable CareAct; Medicaid expansion